The Effectiveness of Quizlet on Teaching Grammar at Eleventh Grade Students of SMA Negeri 1 Bantarsari Cilacap - trunadikara, Warnindah; Dwinalida, Khairunnisa (VISION, 2023)
The problems of this research were students’ difficulties in mastering grammar because of monotonous activity and less interest to learn. Quizlet application was proposed as a new alternative media to engage students’ interest in learning grammar. This study aims to find there was a significant different or not between the experiment class and control class. This study used quasi experimental design and quantitative approach. The population of this research was the eleventh-grade as much as 172students . The sample was chosen by purposive sampling, with 35 students in experimental class and 35 students in control class. This study used pre-test and post-test to collect the data and was analyze used IBM SPSS V 25. The result of Independent Sample T-test showed that the sig.value was 0.298, it means that there was not significant effect. The use of Quizlet to teaching grammar at this school was less effective, but can still use to learn other English subject.